Rapid reversal of anticoagulation prevents excessive secondary hemorrhage after thrombolysis in a thromboembolic model in rats - Sun, Li; Zhou, Wei; Ploen, Robert; Heiland, Sabine; Zorn, Markus; Veltkamp, Roland (Stroke, 2011)
Background and Purpose— - - Thrombolysis is the only approved therapy for ischemic stroke, but secondary hemorrhage is a severe complication. Because oral anticoagulants are believed to increase the risk of hemorrhage, thrombolysis is usually contraindicated in patients on vitamin K antagonists. We studied whether thrombolysis in a thromboembolic middle cerebral artery occlusion model in rats pretreated with warfarin increases secondary hemorrhage, and whether substitution of coagulation factors before thrombolysis prevents hemorrhagic complications. - - Methods— - - Wistar rats were anticoagulated using warfarin in drinking water (0.4 mg/kg per 24 hours). Strength of anticoagulation was monitored using benchside international normalized ratio (INR) coagulometry. Two hours after middle cerebral artery occlusion, recombinant tissue-type plasminogen activator (9 mg/kg) was administered. Two of 5 groups of animals received prothrombin complex concentrate (PCC, 50 U/kg) 15 minutes before thrombolysis. Serial magnetic resonance imaging was performed 20 minutes, 2.5 hours, and 24 hours after middle cerebral artery occlusion. Secondary hemorrhage was quantified on T2* magnetic resonance images as previously established. - - Results— - - Severity of hypoperfusion on initial perfusion-weighted imaging -magnetic resonance did not differ among groups. Thrombolysis resulted in successful reperfusion in all groups. Anticoagulated animals had significantly more secondary hemorrhage and a higher mortality rate compared with nonanticoagulated animals. PCC rapidly reversed the increased international normalized ratio. Although PCC failed to prevent hemorrhage in the strongly anticoagulated, it reduced the incidence of severe hemorrhage in moderately anticoagulated rats (INR, 2-3) to the level of nonanticoagulated controls. - - Conclusions— - - Preceding anticoagulation increases risk and extent of secondary hemorrhage after thrombolysis. Reversal of moderate anticoagulation using PCC may allow thrombolytic therapy without increasing the risk of secondary hemorrhage.
Gesehen am 26.10.2022